Gli strumenti per l'emozione con le innovazioni tecnologiche al servizio di una nuova relazione tra il visitatore e i beni culturali - Donnini, Daniela (Archeomatica, 2014)
The request for culture has evolved. For the visitor is not enough to whatch, she/he wants to interact, get excited while discovering and learning. Touchwindow follow this road towards technological innovation, with years of knowledge at the service of Cultural Heritage to engage and involve visitors. At Touchwindow we research and develop projects and installations, solutions and interactive exhibits. Create systems and software to capture the attention of visitors and lead them along new paths made of visual experience and learning.